"Sequential" boron neutron capture therapy (BNCT): A novel approach to BNCT for the treatment of oral cancer in the hamster cheek pouch model - Molinari, Ana Julia (2011)
In the present study the therapeutic effect and potential toxicity of the novel "â€œSequential"â€ boron neutron capture therapy (Seq-BNCT) for the treatment of oral cancer was evaluated in the hamster cheek pouch model at the RA-3 Nuclear Reactor. Two groups of animals were treated with "Sequential"BNCT, i.e., BNCT mediated by boronophenylalanine (BPA) followed by BNCT mediated by sodium decahydrodecaborate (GB-10) either 24 h (Seq-24h-BNCT) or 48 h (Seq-48h-BNCT) later. In an additional group of animals, BPA and GB-10 were administered concomitantly [(BPA + GB-10)-BNCT]. The single-application BNCT was to the same total physical tumor dose as the "Sequential"BNCT treatments. At 28 days post-treatment, Seq-24h-BNCT and Seq-48h-BNCT induced, respectively, overall tumor responses of 95 ±2% and 91 ±3%, with no statistically significant differences between protocols. Overall response for the single treatment with (BPA + GB-10)-BNCT was 75 ±5%, significantly lower than for Seq-BNCT. Both Seq-BNCT protocols and (BPA + GB-10)-BNCT induced reversible mucositis in the dose-limiting precancerous tissue around treated tumors, reaching Grade 3/4 mucositis in 47 ±12% and 60 ±22% of the animals, respectively. No normal tissue toxicity was associated with tumor response for any of the protocols. "Sequential"BNCT enhanced tumor response without an increase in mucositis in dose-limiting precancerous tissue.